The Myth of Saint Abad: A Study of Sacred Narrative in Barangay VIII, Tuburan, Cebu - Capuyan, Christian; Cantay, Jerwena; Al Hariri, Danah; Charcos, Angen May (International Journal of Language and Literary Studies, 2026)
This study examined the dominant Jungian archetypes and myth values in the Saint Abad myth to explore their cultural and literary significance in Barangay VIII, Tuburan, Cebu. Using a mixed-methods design, a descriptive-quantitative approach surveyed 254 residents, while 30 participants were interviewed in the qualitative phenomenological phase. Quantitative analysis identified four predominant archetypes: Safety, Service, Pleasure, and Power. Safety was most pronounced in the Spiritual Journey category (mean = 3.01), Service in Provision of Structure (mean = 2.93), Pleasure in Connecting Others (mean = 2.74), and Power in Leaving a Mark (mean = 2.62). Qualitative findings revealed that these archetypes shaped respondents’ spiritual beliefs, cultural practices, and daily experiences. Specifically, Power was reflected in the Way of Seeing, Service in the Way of Being, Pleasure in the Way of Earning a Living, and Safety in the Way of Well-being. The study highlights enduring beliefs in supernatural entities and associated practices such as Pangamuyo and Pagdagkot. Findings also underscore the value of integrating localized myths into Philippine literature instruction to foster culturally contextualized learning and appreciation of indigenous narratives.